2005
DOI: 10.1159/000085246
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes and Electrophoretic Studies of Tear Proteins in Tears of Patients with Nasolacrimal Duct Obstruction

Abstract: This study was performed to determine whether there are differences in tear constituents between normal persons and patients with primary acquired nasolacrimal duct obstruction (PANDO) and to correlate differences in tear composition with the degree of PANDO. We tested 30 normal persons (mean age 42.0 ± 21.4 years) and 34 PANDO patients (mean age 44.8 ± 17.9 years) consisting of 18 cases with complete obstruction and 16 cases with partial obstruction. We measured the pH, the concentration of Na+, K<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to previous studies, tear protein components in patients are more alkaline, higher in calcium concentrations and inflammatory cytokines, and unstable compared with normal persons [78]. Kubo et al [9] reported that the tear lipid layer was thicker after dacryocystorhinostomy in four patients (five eyes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, tear protein components in patients are more alkaline, higher in calcium concentrations and inflammatory cytokines, and unstable compared with normal persons [78]. Kubo et al [9] reported that the tear lipid layer was thicker after dacryocystorhinostomy in four patients (five eyes).…”
Section: Discussionmentioning
confidence: 99%
“…Some research has investigated the components of tears in patients with nasolacrimal duct obstruction (NLDO) [78]. According to these previous studies, these tears were more alkaline, had a higher calcium concentration, contained inflammatory cytokines, and were unstable in the proportion of tear proteins compared with normal patients [78]. In 2001, there was a report that tear LLT after dacryocystorhinostomy [9].…”
mentioning
confidence: 99%
“…American College of Physicians, Copyright 2005. All rights reserved 2 Bulmer and Forwell (1956), Kaiser et al (1974) . 3 Chicharro et al (1994) . 4 Lew et al (2005) . 5 Cavaliere et al (1988), Cavaliere et al (1989) . 6 Moritz (2008) . 7 Wheeler et al (1960) . 8 Shiau (1987) . 9 Koo and Gupta (1982), Wack et al (1997) .…”
Section: Salt Dependence Of Chemokine Antimicrobial Activitiesmentioning
confidence: 99%
“…13 Specifically, according to Lew et al, in the tears of PANDO patients, the concentrations of calcium and inflammatory cytokines were higher than those in the tears of normal eyes. 13 In this study, the primary aim was to demonstrate whether MGD can be a cause of persistent epiphora after DCR. In patients with MGD, decreased lipid secretion due to destruction or obstruction of Meibomian glands can lead to evaporative dry eye disease, and reflex hypersecretion of lacrimal glands can be a cause of epiphora.…”
Section: Discussionmentioning
confidence: 95%